PERAN VITAMIN D PADA PROSES PENUAAN KULIT DAN SISTEM SARAF - Cynthia wahyu Asrizal; Fitra fitra (Jurnal Kesehatan, 2024)
Vitamin D, which is actually a hormone, plays a role in various organs of the body. Vitamin D comes from food intake and from the skin when exposed to UVB rays. This vitamin D is then converted into the active form 1,25(OH)2D3 or calcitriol. Calcitriol has a vitamin D receptor (VDR) which is spread across various organs including the skin and nerves. Therefore, vitamin D plays a role in the physiological processes in these organs. Age, lifestyle and external exposure can affect the aging process. Deficiency or insufficiency of vitamin D can disrupt the physiological processes of organs and cause various pathological conditions including the aging process of the skin and nerves. This article reviews the role of vitamin D in the physiological processes in the skin and nerves and its role in the aging process of the skin and nerves.